THE DEPICTION OF THE MAIN CHARACTER'S CHANGE AS A VICTIM OF SEXUAL VIOLENCE IN THE FILM "SPEAK" - Puspaningrum, Galuh; Halim, Abdul (Journal of English Literature and Linguistic Studies, 2025)
This research aims to analyze the main character's change as a victim of sexual violence in the film "Speak" using the semiotics of signs. The focus of this research is to find out and examine the semiotics sign and the meaning in the film “Speak” (2004). This research follows the theory of semiotics sign by Roland Barthes (1968 & 1972). Semiotics is the study of signs and their relationship with other signs and the meaning of signs. This research uses qualitative methods and watching and taking screenshots in the form of pictures or images that will contain paint, action, words, gestures, expressions, and appearances that are part of scenarios or scenes in the film "Speak" as the technique for collecting data. In data analysis, the research took the theory by Miles, Huberman, & Saldana (2014). Semiotic signs obtained in the film "Speak" include positive and negative changes with signs of distrust, anger, helplessness, fear, desperation, self-blame, embarrassment, trust, courage, and self-esteem and also the meaning of these signs concerning the main character's change as a victim of sexual violence. It can be concluded that the signs obtained are interrelated with each other. The changes in the main character are related to the incident, the perpetrator, the environment, and the stigma from outside and within, shown through the thoughts, feelings, and behavior of the victim as a result of a bad experience.